2021
DOI: 10.1177/17531934211051276
|View full text |Cite
|
Sign up to set email alerts
|

Return to work following ultrasound guided thread carpal tunnel release versus open carpal tunnel release: a comparative study

Abstract: A retrospective review of hospital employees at a single employer institution who underwent ultrasound guided thread carpal tunnel release (TCTR) or open carpal tunnel release (OCTR) between January 2018 and August 2020 was performed to ascertain differences in return-to-work status. Patient age, sex, occupation, handedness, severity of carpal tunnel syndrome, prior treatments and surgical outcomes were reviewed. A total of 18 patients underwent TCTR and 17 patients underwent OCTR. The TCTR group averaged 12 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 15 publications
3
15
0
Order By: Relevance
“…Of the 24 included studies for UPCTR, ( Table 8 ) there were four RCTs [ 63 , 64 , 65 , 66 ]: two investigated UPCTR using a hook knife vs. mini-OCTR [ 63 , 64 ]; one compared miniscalpel needles plus steroid injection with corticosteroid injection only [ 65 ]; and one evaluated a U-shaped probe/trough plus 5 mm Dovetail blades vs. OCTR [ 66 ]. There were four case-cohort UPCTR studies [ 17 , 70 , 71 , 72 ]: one compared UPCTR with mini-OCTR [ 17 ]; one investigated UPCTR vs. OCTR [ 72 ]; one evaluated UPCTR using a 22 G hypodermic needle vs. UPCTR plus corticosteroid injection [ 70 ]; and the last case-cohort study compared the use of a UPCTR of an uncoated multifilament stainless steel wire looped thread with no interventions [ 71 ]. Among 16 case series [ 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ], six investigated the effects of different hook knives [ 76 , 79 , 81 , 82 , 87 , 89 ], five evaluated the use of microknives [ 80 , 83 , 85 , 86 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 24 included studies for UPCTR, ( Table 8 ) there were four RCTs [ 63 , 64 , 65 , 66 ]: two investigated UPCTR using a hook knife vs. mini-OCTR [ 63 , 64 ]; one compared miniscalpel needles plus steroid injection with corticosteroid injection only [ 65 ]; and one evaluated a U-shaped probe/trough plus 5 mm Dovetail blades vs. OCTR [ 66 ]. There were four case-cohort UPCTR studies [ 17 , 70 , 71 , 72 ]: one compared UPCTR with mini-OCTR [ 17 ]; one investigated UPCTR vs. OCTR [ 72 ]; one evaluated UPCTR using a 22 G hypodermic needle vs. UPCTR plus corticosteroid injection [ 70 ]; and the last case-cohort study compared the use of a UPCTR of an uncoated multifilament stainless steel wire looped thread with no interventions [ 71 ]. Among 16 case series [ 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ], six investigated the effects of different hook knives [ 76 , 79 , 81 , 82 , 87 , 89 ], five evaluated the use of microknives [ 80 , 83 , 85 , 86 …”
Section: Resultsmentioning
confidence: 99%
“…Guo et al [ 78 ] reported a mean of 17.7 days in their first case series, but in their second case series, the time to return to work was two weeks for manual workers and one day for office workers. Asserson et al [ 72 ] found that the average time of return to work was 12 days in the UPCTR group and 33 days in the OCTR group. Joseph and Leiby et al suggested that patients with occupations requiring repetitive or heavy use of hands could return to light duties one week after UPCTR [ 85 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…TCTR's effectiveness and safety were also confirmed by another group [10]. One study showed its superiority in a shorter return to work compared to open carpal tunnel release, although both were effective [11]. TCTR studies conducted by Danqing Guo et al used a commercial thread (Loop & Shear, 0.23mm in diameter; Ridge & Crest Company, Monterey Park, California) [9,12,13].…”
Section: Introductionmentioning
confidence: 94%
“…In this month’s issue of the Journal, we have several scientific articles centred around CTS. I would like to share some of my thoughts on four of these articles (Asserson et al., 2021; Matsuki et al., 2021; Postma and Kemler, 2021; Ratasvuori et al., 2021).…”
mentioning
confidence: 99%
“…The article by Asserson et al (2021) reports on return to work following carpal tunnel decompression performed using the thread carpal tunnel release method and comparing the results following traditional open carpal tunnel release. This is a relatively novel technique, having been first described 2015.…”
mentioning
confidence: 99%